The Who or the How? Species vs. Ecosystem Function Priorities in Conservation Ecology - Leuzinger, Sebastian; Rewald, Boris (Frontiers in Plant Science, 2021)
Current conservation strategies are targeted at preserving species, without explicitly aiming at the maintenance of ecosystem functions. In a physically highly connected world, the unintentional relocation of terrestrial, marine, and microbial life is therefore unavoidable and has been an integral part of human evolution for thousands of years. Here, we challenge the default perception often shared among conservation ecologists that preserving native species at all cost, and reducing the number of exotic species and their abundance is the only way to conservation and restoration success. While this strategy is valuable in cases where exotic species disrupt ecological function, there are examples where exotic species have similar functional traits to the threatened or extinct native species, and can in fact help maintain the overall or target function of an ecosystem. In the race to cope with global environmental change, we argue that ecosystem function and ecosystem services need to be viewed not only through a taxonomic lens, but increasingly also through a functional, trait-based one.